Timely Diagnosis of Weill-Marchesani Syndrome Can Preserve Vision and Prevent Complication: A Case Report - Ahmed Shahriar, Nafiz; Rani Roy, Soma (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2022)
Purpose: To report a rare case of Weill–Marchesani syndrome with its management. Case Report: A 40-year-old female patient presented with bi-lateral dimness of vision on both eyes, short stature, brachydactyly and joint stiffness. Ocular examination revealed, vision 3/60 in both eyes without improvement with a high myopic correction, bilateral microspherophakia with anterior lens subluxation and normal fundus.She was diagnosed as a case of Weill-Marchesani syndrome and was managed by bi-lateral clear lens extraction followed by secondary anterior chamber intra-ocular lens implantation.Conclusion: Timely diagnosis and by meticulous surgical intervention, complications of Weill-Marchesani syndrome can be managed accordingly.